Effect of Storage Time, Temperature and Region on the Levels of 1, l ,6-Trimethyl-1,2-dihydronaphthalene and other Volatiles, and on Quality of Weisser Riesling Wines - Marais, J.; van Wyk, C.J.; Rapp, A. (South African Journal of Enology and Viticulture, 2017)
A survey of the concentration levels of 1,1,6-trimethyl-1,2-dihydronaphthalene (TDN) in wines of different cultivars, vintages and regions was conducted. The TDN concentrations of South African Weisser Riesling wines were higher than those from Germany and Italy, and those of other cultivars. The effect of storage time and temperature on free and precursor TDN concentrations, on the concentrations of free trans-vitispirane, some monoterpenes, esters and higher alcohols, and on the quality of Weisser Riesling wines was investigated. Three Weisser Riesling wines from different regions were stored at 15°C and 30°C for four years and one year, respectively. These wines were analysed periodically by gas chromatography and evaluated sensorially. The concentrations of TDN, trans-vitispirane, 2,6-dimethyl-7-octen-2,6-diol and trans-1,8-terpin, and the intensity of the bottle-aged kerosene-like character increased significantly with ageing. During the same period, significant decreases occurred in the concentrations of diendiol-1, linalool, i-amyl acetate, ethyl caproate, hexyl acetate, 2-phenethyl acetate, hexanol, 2-phenyl ethanol, and in the intensity of young wine character. alpha-Terpineol showed significant increases followed by decreases under the same conditions. These changes in concentrations were more prominent at 30°C than at 15°C storage. The development of the kerosene character in Weisser Riesling wines was restricted to sensorially acceptable levels by storage at 15°C.